PEMANFAATAN MEDIA SOSIAL UNTUK KEGIATAN DAKWAH - Nurjanah, Citra (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2019)
This article discusses how to use social media for da'wah activities, by analyzing the da'wah process that occurs on Instagram and YouTube social media. The research method is qualitative, namely the collection of data using analysis and a description of the reality of the use of social media for da'wah activities. On Instagram, the preacher who actively preaches is Aa Gym by posting photos, videos, and live broadcasts regularly. Then Ustadz Adi Hidayat Official's YouTube channel is also actively sharing videos and doing live streaming of da'wah studies led by Ustadz Adi himself.